Electrochemical Studies of Stainless Steel Corrosion in Peroxide Solutions - Singh,Ajay K. (2012)
Pollution control measures have resulted in replacement of chlorine by peroxide as bleaching chemical. Change of chemical affects corrosion aspects, the suitability of existing plant metallurgy and materials of construction of bleach plants. Accordingly long term immersion and electrochemical corrosion tests were conducted on stainless steel 304L, 316L, 2205 and 6% Mo and mild steel in peroxide solutions of pH 10. The materials were tested for uniform corrosion, pitting and crevice corrosion and attack around the weld area. Corrosion attack estimated from long term immersion tests is found in agreement, by and large, with that analyzed from electrochemical test. E-pH diagrams drawn for water-peroxide system have been used to understand the corrosivity of the peroxide media. An attempt has been made to suggest a suitable material of construction for handling the test media on the basis of degree of corrosion attack on them and their cost and the mechanical properties.